The Influence of City Branding on Visit Intention, Mediated By Brand Identity and City Image, and Its Impact on Visit Decisions - Rais Akbar; Zainul Arifin; Edriana Pangestuti (Jurnal Mamangan, 2023)
This study examines the relationship between city branding and intention to visit by considering the mediating roles of brand identity and city image, as well as their ultimate influence on the decision to see, through a case study of tourists visiting Makassar City, which is branded as the "City of Delicious Food." This research contributes scientifically to the understanding of culinary-based destination marketing strategies, which are increasingly important in light of the growing competition among cities to attract tourists. Makassar was chosen as the research object because, in 2023, the city launched a new sub-brand highlighting its culinary strengths as a key attraction and element of city identity. Conceptually, this study is grounded in the Theory of Reasoned Action (TRA) and the Theory of Planned Behavior (TPB), which explains the relationship between individual perceptions of a place and the intention and actual behavior to visit. The study adopts a quantitative explanatory approach using Structural Equation Modeling (SEM) with SmartPLS version 4.1.8 software. Data were collected from 150 respondents who have either visited or plan to visit Makassar. The results of the analysis indicate that city branding has a positive and significant influence on building brand identity and city image, which subsequently enhances tourists' intention to visit. This intention was found to have a direct impact on the decision to visit. Furthermore, brand identity and city image play important mediating roles in this relationship. These findings confirm that the attractiveness of a city lies not only in its physical aspects or tourist attractions but also in how all stakeholders, including the government, businesses, and the local community, consistently manage brand identity and city image. In the context of Makassar, emphasizing local culinary richness—such as Jalangkote, Pisang Ijo, Mie Kering, and Pisang Epe—has been proven to be an effective branding strategy in shaping the city's image as a leading culinary destination. Practically, this study guides policymakers in designing destination promotion strategies that leverage local potential, strengthen community participation, and support the development of the creative economy and MSMEs in the region.